EKONOMI INDUSTRIKELAPA SAWIT DI INDONESIA SERTA KAITANNYA DENGAN PROGRAM PENELITIAN DAN PENGEMBANGAN - Teguh Wahyono (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2008)
This paper presents the role of oil palm into national economy, especially into Gross Domestic Product, fiscal earnings, employment, and regional development. Thispaper also brings up research and development program of oil palm, in terms of technology and socio-economic, by considering governmental policy, especially Board of Agriculture Research and Development.